Urban Muslim Widows' Empowerment: Islamic Values-Based Educational Model For Sustainable Development In Hijab Community - Ramadan, Muhammad Ikbal; Kurnianto, Rido; Syam, Aldo Redho; Haq, Muhammad Arinal (Al-madinah: Journal of Islamic Civilization, 2025)
Widows in urban Muslim societies frequently confront significant economic and social vulnerabilities following spousal loss, facing challenges in securing sustainable livelihoods and providing for their families. This study examines the implementation of an Islamic values-based educational strategy within the HIJAB (Himpunan Janda Berkarya) program at PKBM Mutiara Bina Insani, Trenggalek, designed to foster holistic independence. The research aims to analyze the integration of Islamic principles in educational practices and assess its impact on participants' economic, social, and spiritual autonomy. Using a qualitative case study approach, data were collected through in-depth interviews with widows and program facilitators, participatory observation, and document analysis. Findings reveal that the program successfully incorporates Islamic values—such as perseverance (sabr), trust in God (tawakkal), and community responsibility—into practical skill-building and emotional support systems. This integration has enabled widows to develop sustainable micro-enterprises, strengthen social support networks, and enhance their religious identity. The program demonstrates a viable model for faith-based community development, contributing to the socio-economic resilience of urban Muslim families. The study concludes that Islamic value-based educational strategies are effective in promoting comprehensive empowerment, suggesting their potential for replication in similar urban Muslim communities facing parallel challenges of widowhood and economic marginalization.